Research status and hotspots of economic evaluation in nursing by co-word clustering analysis - Liao Yao-Ji; Gao Guo-Zhen (Sciendo, 2019)
The aim of this study is to discover research status and hotspots of economic evaluation (EE) in nursing area using co-word cluster analysis.